Peran Kepala Sekolah Dalam Supervisi dan Evaluasi Pendidikan: Analisis Perspektif Juwdat Izzat Atwi - Edi Rahmat Hidayat; Achmad Muhlis (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2026)
School principals play a strategic role in improving the quality of learning through the implementation of systematic academic supervision and educational evaluation. This article analyzes this role by integrating Juwdat Izzat Atwi's educational management concept in Al-Idarah al-Madrasiyah al-Hadithah with empirical findings from various national studies. Through a comprehensive literature review, this study identifies how Atwi's principles of visionary leadership, strategic planning, ongoing supervision, and data-driven evaluation can be applied in the context of Indonesian schools. The results show that supervision conducted objectively and collaboratively, accompanied by follow-up coaching, can improve teachers' pedagogical competence and learning quality. Conversely, supervision that is solely administrative in nature does not have a significant impact. Educational evaluation has proven to be crucial as a basis for decision-making and program improvement, especially when supported by accurate data analysis. This study concludes that integrating supervision and evaluation within a single Atwi-based management cycle can strengthen internal school quality assurance and support the implementation of the Independent Curriculum. Recommendations are provided for strengthening principal competencies in coaching, data analysis, and the application of professional supervision